Debt restructuring in the UK - Payne, J (De Gruyter, 2018)
Many jurisdictions around the world are seeking to develop an effective mechanism for rescuing financially distressed but viable businesses. In the UK a number of different mechanisms exist which can be used to restructure distressed companies. The purpose of this paper is to assess the debt restructuring mechanisms currently available to companies in English law and to consider the proposed reform of the UK regime, announced by the Government in August 2018. It is argued that reform is needed, and that in general the proposals to introduce a restructuring moratorium and a restructuring plan which includes a cross class cramdown are to be welcomed. However, these reforms will need to be introduced with care in order to ensure that an appropriate balance is maintained between the interests of the company and the interests of the creditors and that, ultimately, the UK’s regime remains fit for purpose for the future.